There are many ways of being a boy: Barbara Kimenye's imagination of boyhood masculinities in selected storybooks from the Moses series - Chabari, Kimathi Emmanuel (My University, 2009)
Abstract This study examines Barbara Kimenye’s imagination of boyhood masculinities in the selected adventure stories from the Moses series. It is based on the understanding that gender is a social construct. The Research Report contributes to children’s literature and gender scholarships. In particular, through textual analysis of primary texts and gender related theoretical framework, I highlight various categories of masculine behaviour based on boy characters’ power, control and popularity at Mukibi Educational Institute – Kimenye’s fictitious boarding school in Moses series. I tease out complexities of both individuals’ and groups’ notions of manliness and how they manifest in various locales. I argue that there are many ways of being a boy. I also highlight how the author deploys satire to imagine a boarding school and how this space allows construction and performance of specific boyhood masculinities. In addition, I highlight Kimenye’s depiction of corporal punishment and family relatives and how these also allow for construction and performance of particular man-like behaviour by her boy characters. Kimenye’s imagination of girlhood masculinities is also explored by examining boy characters’ stereotypes on girls and how through Sekabanja – a girl character – the author manages to deconstruct this by portraying her [Sekabanja] as behaving as expected of a boy. In addition, I highlight Kimenye’s representation of enactment of gender inequalities in a mixed sex school. I also underline how illustrations also participate in the imagination of girlhood masculinities. I argue that by portraying a girl – Sekabanja – as behaving as expected of boys if not better, Kimenye is highlighting gender as a social construct and participating in deconstruction of stereotypes on girls and women through a literary technique.
Keywords: Barbara Kimenye; the Moses series; boyhood masculinities; adventure; illustrations; boarding school; girlhood masculinities